Reinterpretasi Nusyuz dalam Bingkai Mubadalah dan Keadilan Gender dalam Pernikahan - Mahasin, Ashwab; Nihayati, Dini Arifah (Jurnal Antologi Hukum, 2025)
In the context of Islamic Family Jurisprudence (Fiqh al-Usrah), nusyuz is interpreted as a wife’s disobedience toward her husband. The issue of nusyuz in Islamic teachings encompasses the rights and obligations of spouses as well as values of gender equality. This study aims to analyze the relevance of the nusyuz concept within Islamic marital ethics, particularly in relation to the principles of mutuality and gender justice. This is a library-based study employing textual analysis of valid and relevant scholarly works. Using a hermeneutic approach, the research explores various interpretations of nusyuz and its implications for establishing a just and equitable spousal relationship. The findings indicate that a deep understanding of Islamic teachings highlights the urgency of mutual fulfillment of rights and obligations, while upholding gender justice in marital life. Therefore, the concept of nusyuz needs to be reinterpreted to align with Islamic marital ethics based on equality, mutual respect, and fairness for both parties. This study contributes to the discourse on a more progressive and gender-just Islamic family jurisprudence.